A. 4
B. 5
C. 6
D. 7
C
\(\begin{array}{l}\dfrac{{x - 3}}{{3 + i}} + \dfrac{{y - 3}}{{3 - i}} = i\\ \Leftrightarrow \left( {x - 3} \right)\left( {3 - i} \right) + \left( {y - 3} \right)\left( {3 + i} \right) = i\left( {3 - i} \right)\left( {3 + i} \right)\\ \Leftrightarrow 3\left( {x - 3} \right) - \left( {x - 3} \right)i + 3\left( {y - 3} \right) + \left( {y - 3} \right)i = 10i\\ \Leftrightarrow 3\left( {x + y - 6} \right) + \left( {y - x} \right)i = 10i\\ \Leftrightarrow \left\{ \begin{array}{l}x + y - 6 = 0\\y - x = 10\end{array} \right.\\ \Leftrightarrow \left\{ \begin{array}{l}x + y = 6\\y - x = 10\end{array} \right.\end{array}\)
Câu hỏi trên thuộc đề trắc nghiệm dưới đây !
Copyright © 2021 HOCTAP247